PREGNANT WOMEN’S KNOWLEDGE ABOUT BREAST CARE TECHNIQUE - Lilis Mamuroh; Sukmawati Sukmawati; Furkon Nurhakim (Journal of Maternity Care and Reproductive Health, 2019)
Pregnant women need to know how to d9 breast care techniques correctly when breastfeed their babies. The purpose of this study was to determine the description of pregnant women's knowledge about breast care techniques. The study design used quantitative descriptive, the sample in this study were 30 pregnant women selected by accidental sampling method. Data collection was carried out using a questionnaire about breast care knowledge. Location of the research was the Health Post Mekarluyu Sukawening District Garut Regency, the data were analyzed using univariate statistical tests. Research results found that most respondents have moderate knowledge about breast care and there were respondents who have low level of knowledge. The age of respondents was mostly 20-30 years, the majority of respondents attended elementary school, and they were prim-gravida. Conclusions some respondents have moderate knowledge, and there are still respondents with low levels of knowledge. Suggestions, it is expected that health workers improve services in the form of health education to pregnant women with less knowledge about breast care techniques.Keywords: Breast care, knowledge, pregnant women.